Tumor-targeting nanomaterials based on metal-organic frameworks mediate tumor immunotherapy by promoting cuproptosis and pyroptosis in hepatocellular carcinoma cells - Xiaoyuan Yi; Huaying Xie; Kunzhao Huang; Jianzhang Luo; Wen Li; Qingyu Zeng; Feifei He; Wuxiang Shi; Duo Wang; Liyan Wang (Materials Today Bio)
Activating a robust immune response is an effective strategy for achieving tumor eradication. In this study, copper-based metal-organic framework nanoparticles (referred to as FA-PZ@MOF NPs), which have the ability to simultaneously induce cuproptosis and pyroptosis in tumor cells, were designed to utilize the synergistic effects of cuproptosis and pyroptosis to trigger immunogenic cell death (ICD). This can inhibit tumor growth, migration, and metastasis while enabling efficient antitumor immunotherapy. The nano inducer targets hepatocellular carcinoma tumor cells via folic acid, dissociates and releases copper ions in the tumor microenvironment (TME), which has a high glutathione concentration, leading to copper ion overload, thereby mediating cuproptosis. Additionally, the released ZnO2 generates substantial amounts of H2O2 and Zn2+ in the acidic environment, enhancing the Cu2+-based Fenton-like reaction for chemokinetic therapy. This exacerbates the reactive oxygen species (ROS) storms and mitochondrial damage, and combined with the action of Polyphyllin VI (PPVI), induces pyroptosis and cuproptosis. This multilayered interaction strategy also triggers robust ICD while inhibiting hepatocellular carcinoma tumor metastasis and invasion.